2020
DOI: 10.1029/2020gl087607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on Lattice Thermal Conductivity of Ringwoodite and Its Implications for the Thermal Evolution of Descending Slabs

Abstract: The presence of water in minerals generally alters their physical properties. Ringwoodite is the most abundant phase in the lowermost mantle transition zone and can host up to 1.5–2 wt% water. We studied high‐pressure lattice thermal conductivity of dry and hydrous ringwoodite by combining diamond‐anvil cell experiments with ultrafast optics. The incorporation of 1.73 wt% water substantially reduces the ringwoodite thermal conductivity by more than 40% at mantle transition zone pressures. We further parameteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 78 publications
6
39
0
Order By: Relevance
“…Note that for both Al-phase D and (Al,Fe)-phase D, the thermal conductivity in each measurement run (different crystal orientation) is similar to each other, suggesting that the effect of crystal orientation on their thermal conductivity is negligible. Furthermore, similar to the ferropericlase (W.-P. Hsieh et al, 2018) and δ-(Al,Fe)OOH (W.-P. Hsieh et al, 2020), we observed an enhanced impurity effect of iron in the low-spin Fe-bearing phase D, that is, compared to the high-spin state, the thermal conductivity of low-spin Fe-bearing phase D is much lower than that of the Fe-free phase D.…”
Section: High-pressure Room-temperature Thermal Conductivity Across S...supporting
confidence: 75%
See 2 more Smart Citations
“…Note that for both Al-phase D and (Al,Fe)-phase D, the thermal conductivity in each measurement run (different crystal orientation) is similar to each other, suggesting that the effect of crystal orientation on their thermal conductivity is negligible. Furthermore, similar to the ferropericlase (W.-P. Hsieh et al, 2018) and δ-(Al,Fe)OOH (W.-P. Hsieh et al, 2020), we observed an enhanced impurity effect of iron in the low-spin Fe-bearing phase D, that is, compared to the high-spin state, the thermal conductivity of low-spin Fe-bearing phase D is much lower than that of the Fe-free phase D.…”
Section: High-pressure Room-temperature Thermal Conductivity Across S...supporting
confidence: 75%
“…TDTR has been a well-established ultrafast optical pump-probe method that enables precise measurement of thermal conductivity at ambient and high pressures, see, for example, (Y.-Y. Chang et al, 2017;W.-P. Hsieh et al, 2018;W. P. Hsieh et al, 2020).…”
Section: Lattice Thermal Conductivity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory measurements of sound wave velocities (compressional (V P ) and shear wave (V S ) velocity) of minerals at high P -T play a central role in enabling scientists to constrain the constitution, composition, and potential hydration state of the Earth's mantle via a comparison with the velocity profiles derived by seismological observations. The elastic properties of olivine, wadsleyite, and ringwoodite have been studied by using various techniques, including Brillouin spectroscopy (e.g., Sinogeikin et al, 2003), ultrasonic interferometry (e.g., Li, 2003;Higo et al, 2008;Li and Liebermann, 2014), resonant sphere technique (Mayama et al, 2005), and theoretical calculations (e.g., Núñez Valdez et al, 2012;Wang et al, 2019). However, most such measurements have been made at high/or room temperature and ambient pressure (Jackson et al, 2000;Jacobsen et al, 2004) or at high pressure and room temperature (Zha et al, 1996;Li et al, 1996;Li and Liebermann, 2000;Li, 2003;Darling et al, 2004;Jacobsen and Smyth, 2006;J.…”
Section: Sound Velocitymentioning
confidence: 99%
“…Lattice thermal conductivity, the ability of a material to conduct heat, of minerals in the mantle and subducting slabs is crucial to control the thermal evolution and geodynamics in Earth's interior (Chang et al, 2017;Dalton et al, 2013;Deschamps and Hsieh, 2019;Hsieh et al, 2017;Hsieh et al, 2018;Hsieh et al, 2020;Marzotto et al, 2020). Recent studies suggested that a temperature anomaly within a subducting slab could be induced by large variations of thermal conductivity in the oceanic crust due to, for instance, the effect of hydration (Chang et al, 2017) or spin transition (Chao and Hsieh, 2019;Hsieh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%